Development of 18F-Labeled Resazurin Derivatives for the Detection of Tumor Metabolic Activity Using Cerenkov Imaging - Arroyo, Alejandro D.; Guzman, Andrea E.; Kachur, Alexander V.; Popov, Anatoliy V.; Delikatny, E. James (Frontiers in Physics, 2021)
This paper describes functional fluorinated bioactivatable molecules to study cancer metabolism using Cerenkov imaging. Resazurin (RA), or Alamar Blue, is a commonly used viability dye and redox sensor. Under reductive conditions or by the action of NADH dehydrogenases, RA is reduced into resorufin (RAred), a highly fluorescent molecule. Cold- and radio-labeled monofluorinated resazurin (MFRA) were synthesized using electrophilic fluorination. The fluorescence of the reduced probe allowed for the detection of Cerenkov Radiation Energy Transfer (CRET). Cerenkov imaging of MFRAred showed a 4-fold increase in signal at 640 nm relative to MFRA, demonstrating the ability to differentiate between oxidized and reduced species via optical imaging. CRET allows the measurement of signal at longer wavelengths closer to the near infrared (NIR) window, ideal for in vivo imaging. MFRA reduction showed different rates in two breast cancer cell lines: MDA-MB-231, a triple-negative breast cancer, and 4175-Luc+, an aggressive MDA-MB-231 variant, isolated from murine lung metastases. 4175-Luc+ cells showed a more rapid reduction of RA and MFRAox than MDA-MB-231 cells. Intratumoral injections of 18F-FDG/MFRA showed a faster reduction of the probe in 4175-Luc+ tumors than in MDA-MB-231, suggesting that the metabolic feature observed in the cells is maintained in the tumors. MFRA is a promising probe to determine tumor energy imbalance, reductive environments and assess metastatic potential of tumors. Furthermore, the use of 18F-labeled probes allows for dual modality PET/Cerenkov imaging for probe localization and biodistribution while assessing probe reduction simultaneously.